Jaringan Komunikasi Anak Jalanan Berkaitan dengan Diterapkannya Sistem Satu Arah di Kota Bogor - Reinhard Hutabarat; Dwi Rini Sovia Firdaus; Ismail Taufik Rusfien (Jurnal Penelitian Sosial Ilmu Komunikasi, 2019)
Abstract          This research is a qualitative descriptive study that aims to determine the communication network of street children in connection with the implementation of a one-way system in the city of Bogor. It also finds out whether street children are one of the inhibiting factors in implementing a one-way system in the city of Bogor. The communication network described in this study is the structure of the wheeled communication network, the chain communication structure, the communication structure of the Y communication network, the circle network structure, and the communication network structure of all channels. Data sources used in this study are key informants, informants, events and activities, and literature related to group communication and communication networks. The sampling technique in this study was purposive sampling which was considered to know accurate information in response to the research problem formulation. Data collection techniques using in-depth interviews and observation techniques, while data analysis techniques used using interactive analysis models include: collection, data reduction, data interpretation, and drawing conclusions after verification. Based on the results of the study, communication networks are used by groups of children in the street that became the informant in this study. The first informants were from Tugu Kujang with chain communication network structure. The informants with wheel communication network structure are from Taman Topi, Lodaya, and Bantar Kemang. Street children are not directly inhibiting factors for the implementation of a one-way system in the city of Bogor, yet impeding aesthetics and the order of the city. The government conducts periodic training and provides a Work Training Center on a regular basis and provides Job Training Centers to reduce the growth rate of street children in Bogor city.  Keywords: anak travel bogor, bogor city, communication network one-way system